A Novel Synthesis Method of La–Mg‐Ni‐based Superlattice by LaNi5 Absorbing Gas‐state Mg. Issue 27 (22nd July 2019) - Zhao, Xin; Ke, Dandan; Cai, Ying; Hu, Feng; Liu, Jingjing; Zhang, Lu; Han, Shumin
Abstract: La−Mg‐Ni based alloys are considered as future negative material for Ni‐MH batteries, while the volatilization of Mg hinders their application. Mg volatilization is considered irreversible in the preparation process. Herein, we provide a novel process to produce superlattice La−Mg‐Ni‐based alloy via alloying gas‐state Mg with LaNi5 slice. The formation of superlattice structures is verified in detail by microstructure characterization and element distribution analysis. The results indicate that there exists an equilibrium state for Mg solution in the La−Mg‐Ni alloy, and the gas‐state Mg atoms are directly absorbed by the LaNi5 alloy. With increasing the absorption time, Mg in LaNi5 slice bends to become more homogenous. It is attributed that the integration of the gas‐state Mg atoms leads to the transformation of the crystal structure of the LaNi5 cells on the slice surface into MgCu4 Sn‐type phase, thus the solid LaNi5 phase turn to liquid MgCu4 Sn‐type phase under the high temperature. Further, the liquid phase permeates into the inside of the LaNi5 slice along crystal boundaries which alloys with LaNi5 lattices to form Ce2 Ni7 ‐type phase. This technology proves that the migration of metal atoms in gas state can induce a regroup phenomenon to form solid state crystal and provides a brand method for hydrogen storage materials preparation. Abstract : A novel process to produce superlattice La−Mg‐Ni‐based alloy via alloying gas‐state Mg with LaNi5 slice was employed to study the Mg diffusion mechanism in LaNi5 alloy. The study suggests that there exists an equilibrium state for Mg solution in the La−Mg‐Ni alloy, and the gas‐state Mg atoms are directly absorbed by the LaNi5 alloy.